Endoscopic Transcortical Selective Amygdalohippocampectomy for Mesial Temporal Lobe Epilepsy: 2-Dimensional Operative Video. Issue 5 (28th July 2021) - Uda, Takehiro; Kawashima, Toshiyuki; Hattori, Masato; Kojima, Yuichiro; Mito, Yuki; Goto, Takeo
Abstract: This surgical video shows a 19-yr-old woman with focal impaired awareness seizures. Seizure semiology showed no lateralizing signs. Ictal electroencephalography (EEG) failed to determine the seizure origin. Interictal EEG showed bilateral spike-and-waves at the temporal electrodes. Magnetic resonance imaging (MRI) showed suspected hippocampal sclerosis on the right side. To determine the side of the focus, depth electrodes were implanted in both hippocampi. Invasive video EEG identified the seizure origin on the right. The decision was made to perform selective amygdalohippocampectomy (SelAH) via the middle temporal gyrus (MTG). An endoscope was used to minimize the craniotomy and shorten the skin incision. A 5-cm linear skin incision and 2.5-cm craniotomy were made. A thin tube was inserted to the inferior horn of the lateral ventricle (Inf-H) under neuronavigation to guide the route to the Inf-H. The endoscope was introduced. A 1.5-cm corticotomy was made at the MTG, and white matter was aspirated until opening the Inf-H. The hippocampus and parahippocampal gyrus were removed with the usual steps in microsurgical SelAH. The surgical time was 4 h 20 min. The patient was discharged without complications and has remained seizure free. In addition to the preoperative objectives, using an endoscope widens the surgical view in the Inf-H compared with microsurgical procedures. Although seizure and cognitive outcomes are expected to be comparable to those from other methods of SelAH, invasiveness might be reduced. This appears to represent the first video report of endoscopic SelAH. The patient consented to the procedure and publication of her images and surgical video.